Moving forward against misinformation or stepping back? WhatsApp’s forwarded tag as an electronically relayed information cue - TANDOC, Edson C. (Institutional Knowledge at Singapore Management University, 2022)
WhatsApp, currently the leading messaging application in the world with an estimated 2 billion users, introduced the forwarded tag in July 2018. When WhatsApp users send messages that they received from someone else, a tag appears with the message to indicate it has been forwarded. By alerting receivers that the message was not written by the immediate sender and was merely passed along, the forwarded tag may trigger skepticism of, and efforts to, verify the message contents. But does it? This study conceptualizes the forwarded tag as an electronically relayed information cue (ERIC) and seeks to answer that question using a mixed-methods study conducted in Singapore. This study combines data from an online experiment (n = 266) and individual and group interviews (n = 65) in a sequential explanatory design. The online experiment found participants rated a WhatsApp message as less credible when it was accompanied by a forwarded tag, whereas the interviews found users associate the forwarded tag with originality and sincerity.